A Frequency optimized architectural approach to lightweight authenticated encryption algorithm ACE-128 - Srikanth, Medaboyina; Patnaik, Bijayananda; Acharya, Bibhudendra (2025 Fourth International Conference on Power, Control and Computing Technologies (ICPC2T), 2025)
Communication stands out as a vital function facili tated by the Internet of Things (IoT), making the secure transfer of data from origin to destination crucial. Traditional encryption methods can accomplish this task, but they often require a trade off between cost, security, and efficiency. In contrast, lightweight encryption provides an effective balance of robust security, affordability, and enhanced performance. Moreover, the reduced data volume involved in lightweight encryption decreases the chances of successfully breaching the cipher. The ACE cipher, a 128-bit lightweight authenticated encryption algorithm, employs a 320-bit(40-bytes) internal state and operates in a unified sponge duplex configuration. The architecture proposed has been tested and implemented across various FPGA families, showcasing an increase in operational frequency.